PREVENTION OF DIARRHEA IN CHILDREN THROUGH PLAY AS A HEALTH PROMOTION EFFORT: SYSTEMATIC REVIEW - Fransiska Novita Sari; Ni Luh Putu Dian Yunita Sari; Koko Wahyu Tarnoto (Indonesian Journal of Community Health Nursing, 2023)
ABSTRACT Introduction: Diarrhea is a health problem that children are prone to. Currently, prevention efforts with media games are still rare. The purpose of this study was to examine game educational media in an effort to prevent diarrhea in children. Method: The method in this research is a systematic review. The stages of article selection use the PRISMA guideline. The results obtained are that there are ten articles that are feasible to be analyzed. Result: The results include journal from the search database Sage, Science Direct and Taylor & Francis using 12 journal There are three themes found, namely the types of games used in health promotion for preventing diarrhea, the age group of children, and health promotion settings. Conclusion: This research is expected to be the basis for community nurses to develop educational media that are interesting and effective in preventing diarrhea in children. Keywords: diarrhea, children’s games, health promotion